Blood will tell : [large type] a novel - Chavez, Heather (Harper Large Print, an imprint of HarperCollins Publishers, 2022)
"From the author of the acclaimed debut No Bad Deed, a twisty novel about the bond between two sisters--and the crimes one covers up to protect the other."--